Studi Banding dan Penyuluhan tentang Standarisasi & Pemasaran Gula Semut di CV Agro Berdikari, Kebumen - Endang Wahyuningsih; Nurlaila Fatmawati; Nunur Nuraeni; Risky Bayu Adhitya; Abdul Hakim (Jurnal Pengabdian Masyarakat, 2025)
One of the coconut palm sugar producers in Jintung Village, Ayah District, Kebumen Regency is the “Brayo Makmur Jintung” Sugar Craftsmen Group. Palm sugar production is the daily livelihood of this group's members. Coconut palm sugar has good prospects abroad, especially in the Americas and Europe. This of course must also meet strict standards and provisions. The lack of knowledge of coconut palm sugar craftsmen “Brayo Makmur Jintung” regarding palm sugar standardization, encouraged the UMNU Kebumen community service team to carry out the “Comparative Study and Counseling on Palm Sugar Standardization and Marketing” activity held at CV Agro Berdikari Sempor, Kebumen. The activity aims for palm sugar craftsmen to gain new knowledge and experience regarding palm sugar standardization according to market demand and learn about palm sugar marketing strategies so that it can be accepted abroad. The method of implementation of this program is counseling and field observation. Craftsmen received information regarding palm sugar standardization that has been implemented at CV Agro Berdikari Sempor. In addition, they were also invited to tour to directly observe the palm sugar production process there. The results of the activity showed that the artisans were enthusiastic about participating in the presentation on palm sugar standardization. They also witnessed firsthand and understood the palm sugar industry process at CV Agro Berdikari Sempor, from receiving the palm sugar from farmers to packaging. This program successfully encouraged the farmers to produce palm sugar to better standards and to develop plans for various flavors.